The Effect of Work Discipline on Employee Productivity - Hutauruk, Friska Juliana; Matondang, Rahim; Pujangkoro, Sugiharto (TALENTA Publisher, 2022)
The workforce has an important role in increasing production at PT. XYZ. The contribution of labor is interpreted into the resulting productivity. Therefore, it is important to know what variables can affect labor productivity. in this study using work discipline variables to see its effect on employee productivity. The results obtained that work discipline has a positive and significant effect on employee productivity, which is 66.70%. and 33.30% possibility of being influenced by other variables not included in this case.